2007
DOI: 10.1139/p07-088
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Odin–SMR ozone profiles with ground-based millimetre-wave observations in the Arctic, the mid-latitudes, and the tropics

Abstract: The sub-millimetre radiometer (SMR) on board the Odin satellite measures signatures of ozone in two bands centred at 501.8 and 544.6 GHz. From the measurements, ozone volume mixing ratio profiles in the stratosphere and lower mesosphere are retrieved using the Optimal Estimation Method. In this paper, the ozone profiles measured by Odin-SMR (level-2 data ver. 2.1 and 2.0, respectively) are compared to measurements taken by ground-based millimetre wave radiometers in the Arctic; at Kiruna, Sweden; in the mid-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…16b) demonstrate slightly higher ozone values: 4-4.5 ppmv in January and 5 ppmv in March. The lower ozone mixing ratios registered by Odin compared to Aura, are in agreement with results by Kopp et al (2007) who have demonstrated about 20-30% lower ozone values from Odin in the middle stratosphere compared to the ground-based measurements. The wavenumber one oscillations (Figs.…”
Section: Comparison Of the Zonal Means Wavenumber Onesupporting
confidence: 92%
See 1 more Smart Citation
“…16b) demonstrate slightly higher ozone values: 4-4.5 ppmv in January and 5 ppmv in March. The lower ozone mixing ratios registered by Odin compared to Aura, are in agreement with results by Kopp et al (2007) who have demonstrated about 20-30% lower ozone values from Odin in the middle stratosphere compared to the ground-based measurements. The wavenumber one oscillations (Figs.…”
Section: Comparison Of the Zonal Means Wavenumber Onesupporting
confidence: 92%
“…Validation of ozone data from Odin SMR using the 544.9 GHz line was performed in the experimental work by Kopp et al (2007). This showed that the Odin measurements contain a systematic bias of 20-30% lower ozone mixing ratios in the middle stratosphere compared to the groundbased measurements.…”
Section: Odin Smr Datamentioning
confidence: 98%
“…Validation of the Odin ozone data has been reported by Kopp et al (2007), who made an intercomparison of Odin-SMR ozone profiles with ground-based ozone observations. The results showed that the Odin measurements at 544.9 GHz yielded a systematic bias of 20-30% lower ozone mixing ratios in the middle stratosphere than the groundbased measurements.…”
Section: Data Sources and Technique Of Data Analysismentioning
confidence: 99%